Investigation of archaeometallurgical findings from Felix Romuliana locality - Živković D.; Štrbac N.; Lamut J.; Anđelić B.; Cocić M.; Šteharnik M.; Mitovski A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Remains of metallurgical activities have been discovered recently at the locality Felix Romuliana near Zaječar (Eastern Serbia), with a lot of slag occurrences and metal findings. Samples, taken from this locality, have been investigated using different characterization methods - chemical analysis, XRD and SEM-EDX, in order to clarify the Early Byzantine metallurgical activities at Felix Romuliana.